Randomized Trial of Dietary Acid Reduction and Acid-Base Status of Patients With CKD and Normal Estimated GFR - Nimrit Goraya; Nicolaos E. Madias; Jan Simoni; Maninder Kahlon; Nazan Aksan; Donald E. Wesson (Kidney International Reports)
Introduction: Modern acid-producing diets in patients with stage G3 to G5 chronic kidney disease (CKD) can cause severe acid accumulation with metabolic acidosis and less severe accumulation causing eubicarbonatemic acidosis in stages G2 to G3, each with kidney injury. The impact of these diets on acid accumulation in those with CKD but normal estimated glomerular filtration rate (eGFR) (CKD G1) is unclear. Methods: We assessed whether acid accumulation occurs in patients with CKD and normal eGFR, and if added base-producing fruits and vegetables (F&Vs) or oral sodium bicarbonate (NaHCO3) (HCO3−) reduces acid accumulation and/or lowers kidney injury. We randomized 153 participants with macroalbuminuric, nondiabetic, CKD stage G1 (mean eGFR = 101 ml/min per 1.73 m2) with hypertension-associated CKD to receive F&Vs in amounts to reduce dietary acid intake by 50% (F&V, n = 51), oral NaHCO3 to match alkali intake of F&V (HCO3−, n = 51), or usual care (UC, n = 51) for 5 years. We assessed acid accumulation by comparing observed to expected increase in plasma total CO2 (PTCO2) in response to retained bicarbonate (dose − urine bicarbonate excretion) 2 hours after an oral NaHCO3 bolus. Results: Baseline acid accumulation, eGFR, urine excretion of albumin, N-acetyl-β-D-glucosamine, and angiotensinogen were not different among groups. Five-year acid accumulation (mean [SD]) was lower in F&V (−1.2 [11.0] mmol] and in HCO3− (−1.7 [10.8] mmol) than in UC (5.2 [10.3] mmol, P < 0.003), which is consistent with lower acid accumulation in F&V and HCO3−. Five-year urine excretion of albumin, N-acetyl-β-D-glucosamine, and angiotensinogen were lower in F&V and HCO3− than in UC, which is consistent with less kidney injury. Conclusions: Dietary acid reduction reduces acid accumulation and kidney injury in patients with CKD and normal eGFR.